RAINWATER HARVESTING FOR FISH FARMING WATER REQUIREMENTS IN BOYOLALI REGENCY, INDONESIA - Hadiani, Rintis; Septiariva, Iva Yenis; Solichin, Solichin; Muttaqien, Adi Yusuf; Sudarto, Sudarto (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2021)
Climate change causes dry and rainy seasons to shift. Hydrology also shows that the number of rainwater changes with the uncertainty of its potential occurrence. In catfish farming and hydroponic farming, ensuring water availability is important for the sustainability of the project. Existing research is about managing rainwater, which can help partially supply water for both projects' benefit. The research location is in Jeron Village, Nogosari District, Boyolali Regency. Boyolali Regency is a 22 % residential area of the total area. It means 570 m3 potential storage. However, the result shows that only 17% of the roof area can collect rainfall for residential houses. In this study's residential case example, 17% of the roof area gives 97.8 m3 / year. The problem is that currently, there is no Rain Water Harvesting (RWH). A system capable of supporting the water supply. Using RWH provides a benefit based on the potential supply. This study highlights the potential benefits of using RWH. This pool yields a profit of up to (Indonesian Rupiah) IDR. 36,643,718 / month or IDR. 439,724.61 / year, with a probability of 80%. It means that in 5 years, it failed once. Moreover, water needs can supply from RWH.